The Influence of International Legal Frameworks on Peacebuilding in the Bangsamoro Region: An Assessment of Acceptance, Perception, and Application - Fazlurrashed S. Paslangan; Laniel Ryan P. Untong (Randwick International of Social Science Journal, 2026)
This study explores how International Humanitarian Law (IHL), International Human Rights Law (IHRL), and Islamic Law intertwine to shape peacebuilding in the Bangsamoro Autonomous Region in Muslim Mindanao (BARMM). Drawing on deep-dive interviews with eight influential leaders from state security forces, non-state armed groups, and regional governance bodies, the research uncovers a complex legal landscape where global standards meet deeply rooted faith. The findings reveal that while international frameworks are respected for their operational utility in limiting conflict and building trust, Islamic Law remains the heartbeat of the region’s identity and the primary lens through which justice is understood. This acceptance, however, exists in a delicate balance—it is "identity-driven" yet "conditional," navigating the boundaries of the Philippine Constitution and the practicalities of regional autonomy. On the ground, this manifests in fascinating hybrid systems: non-state actors maintain discipline through religious guidance (Mursidin) and Sharia-based boards, while the regional government champions "Moral Governance" to align state duties with spiritual values. Ultimately, the study highlights that for human rights and humanitarian principles to truly take root, they must be contextualized within local religious and cultural narratives. By recommending the harmonization of these legal systems, the strengthening of Sharia courts, and community-led education, the research argues that the path to sustainable peace and social cohesion in Bangsamoro lies in honoring the resonance between international law and the Islamic faith to protect the dignity of every individual.